Adult Education in the End of the Century: A Reflective Review from Portugal - A. Fragoso; E. Lucio-Villegas (Adult Education Research Conference, 2000)
In this paper we review adult education policies in Portugal from 1974 until 1999, and we also try to provide a realistic portrait of the current situation. Our main aim is to give suggestions to guide researchers in this field of work.